Old Age Homes: Reasons for Admission and Assessment of Health-Related Quality of Life of Inmates - Dixit, Sanjay; Bansal, SB; Banzal, Sonal; Raja, Roshini Saleem; Dua, Shivani; Agrawal, Rudri (National Journal of Community Medicine, 2015)
Background: Aging is a normal phenomenon, and there had been a demographic transition which has led to the continuous increase in elderly population. As this group of people is more vulnerable to various health problems, therefore a study was carried out with following objectives. Objectives: To study the reasons responsible for elderly opting for old age homes and Health related quality of life (HRQOL) of people living in old age homes. Methods: A cross sectional study was done on 195 participants living in the old age homes. A semi structured questionnaire was used to assess socio-demographic profile and factor responsible for elderly opting for old age homes. The Chi square test with Yates correction was applied. Results: A total of 195 elderly, 99 males and 96 females, were interviewed. The mean age of the subjects was 78.12. A majority of the population (83.07%), came to these old age homes by their own will because they didn’t have anybody to look after them (68.20%). 41.90% subjects had an improvement in their health status in the past one year, 54.30% subjects felt that there could not get any worse. Conclusion: The Elderly populations came to the old age home because of loneliness, didn’t had anyone to look after them, had no place to live, didn’t want to be a burden on anyone and wanted an independent life. Mild to moderate body pain and physical health or emotional problems were commonest problem experienced by participants.